2021
DOI: 10.1037/emo0001007
|View full text |Cite
|
Sign up to set email alerts
|

What constitutes a compassionate response? The important role of culture.

Abstract: American compassionate responses (i.e., sending sympathy cards) focus more on the positive (e.g., comforting memories) and less on the negative (e.g., the pain of someone's death) than German compassionate responses, partly because of cultural differences in how much people want to avoid feeling negative (i.e., avoided negative affect [ANA]). However, are these culture-specific compassionate responses considered more comforting and compassionate within their respective cultural context? We predicted that Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…To understand why potential cultural differences might emerge, we also assess ANA (which is culturally shaped; Koopmann-Holm & Tsai, 2014). We examine whether the association between ANA and conceptualizations of compassionate faces, which previous research has found among U.S. American, German, and Chinese samples (e.g., Koopmann-Holm et al, 2021), replicates when we include an Ecuadorian sample. Furthermore, because past research has not yet examined the mechanism through which ANA shapes conceptualizations of a compassionate face, the present work starts to explore this process.…”
Section: The Present Researchmentioning
confidence: 86%
See 4 more Smart Citations
“…To understand why potential cultural differences might emerge, we also assess ANA (which is culturally shaped; Koopmann-Holm & Tsai, 2014). We examine whether the association between ANA and conceptualizations of compassionate faces, which previous research has found among U.S. American, German, and Chinese samples (e.g., Koopmann-Holm et al, 2021), replicates when we include an Ecuadorian sample. Furthermore, because past research has not yet examined the mechanism through which ANA shapes conceptualizations of a compassionate face, the present work starts to explore this process.…”
Section: The Present Researchmentioning
confidence: 86%
“…These cultural differences generalize to what kind of faces people consider to be compassionate. While for U.S. Americans, a face with a slight smile is considered compassionate, for Germans, a face with a somewhat sad and distressed expression is considered compassionate (Koopmann-Holm et al, 2021). Another line of research suggests that like Germans, Chinese participants consider a face with a somewhat sad and distressed expression as more compassionate compared to U.S. Americans (Seow et al, 2024).…”
Section: Is Compassion Universal?mentioning
confidence: 99%
See 3 more Smart Citations